Sustainable procurement behaviour in public service: the impact of green organizational culture and commitment towards change - Nadeem, Shahid (2017)
Globally the issues related to sustainability are recognized, and efforts are made by nations to meet the challenges. To address this issue, a new global trend of Sustainable Public Procurement (SPP) has emerged lately. However, in developing economies particularly in the region of South Asia the pace of implementation of SPP is low. Lack of Sustainable Procurement Behaviour (SPB) of procurers is considered as one of the major barrier for its implementation. This study investigate the effects of Personal Values (PV), Awareness (AW), Public Service Motivation (PSM) and Leadership Style (LS) on SPB in Pakistan. Moderating influences of Green Organisation Culture (GOC) and mediating effects of Commitment towards Change (CTC) on the relationship of these variables were also examined. In this quantitative study, the data were collected from 250 managers working in the government departments of Punjab in Pakistan by using a cross sectional design. The study adopted a simple random sampling technique on randomly selected respondents (procurement managers). Partial least Squares Structural Equation Modelling (PLS-SEM) was used to test the study hypothesis. This study found that AW and PV of managers positively influence the SPB however, LS and PSM has no influence on SPB. Furthermore PV and AW influence the level of CTC but LS has no influence on CTC. Moreover, GOC has significant moderating influence between CTC and SPB. The research findings filled the void of knowledge in the field of SPB in public sector in Pakistan. The results of this study offers important insights to policymakers, procurement managers and researchers to further understand and improve the SPB of the managers in Pakistan.